Perbedaan Tingkat Organizational Citizenship Behavior (OCB) Ditinjau dari Tahap Perkembangan Karir Karyawan PT Tirta Investama (AQUA) Pandaan - Putra, Muhammad Khasbulloh Megananda; Djudiyah, Djudiyah (Cognicia, 2019)
Each stage of career development raises special characteristics that are not had by other stages of career development. These characteristics are seen to be related to the dimensions of OCB which will then affect the employee's OCB as a whole. Establishment stage, someone who is at the age of 25-44 years where the person tries to adapt at work. Maintenance stage, someone who is at the age of 45-64 years who feels comfort in his job position, will take care and maintain the position as best as possible. This study aims to determine whether there are differences in OCB levels reviewed based on the stages of career development. This study uses comparative quantitative research. Data collection techniques using purposive sampling with a total sample of 60 employees divided into two sample groups, namely 30 employees aged 25-44 years and 30 employees aged 45-64 years. Data retrieval uses the OCB scale. Obtained the results of the analysis of independent sample t test with a t count value of 6.198 and a probability of 0.000, these results indicate that OCB are have significant differences in terms of the stage of career development.